Energy-saving window systems: types, development, comparisons and perspectives - Riabinina, Yu. S.; Tsyfra, T. Yu. (Ways to Improve Construction Efficiency, 2020)
The tendency to use natural resources is decreasing; energy conservation and ecosystems are taking the first positions. Therefore, the use of glass finishing of buildings has become a starting point in the search for new technologies to save energy use, reduce the need for air conditioning and additional lighting. The developed smart glass is an advanced type of glass that can change transparency depending on different conditions, or convert sunlight into electricity that can be used for human needs. The work examines the appearance of the first types of smart windows, and further development of smart windows using various films, chemical and organic compounds. The prospect of using smart glass to improve natural lighting in various fields and the future possibilities of related technologies by comparing several types of smart glass. The main types of smart windows are presented: photochromic window, thermochromic window, electrochromic window, liquid crystal windows, windows based on suspended particles, window using a "thermal mirror". On the basis of the given characteristics of various technologies of smart glass, its advantages and disadvantages, as well as the associated difficulties, which should be resolved in the future, are revealed. The existing classification of smart windows by the type of use of films in them and their advantages and disadvantages of using. The main newest technologies of absorption of sunlight by the surface of the window and the conversion of light into electricity, the problem of achieving transparency by glass, and the tendency of solving this issue are described. On specific examples, the areas of application of glass with controlled transparency are considered, and the economic indicators obtained when it is used in buildings. The technology of using solar panels in the form of blinds and their influence on providing the building with energy is considered. improvement of some of its optical properties, contributed to a decrease in its cost, which leads to an increase in the availability of this material.